Viburnum spp.: examining the relationship between greenhouse-growth studies for heat and drought tolerance to determine correlation to landscape survival - Pool, Joshua Roy (Kansas State University, 2019)
Three studies were designed to evaluate Viburnum spp. and their physiological adaptation to drought, heat, and other environmental stresses found in the Great Plains, specifically Kansas. Nursery crop growers, landscape contractors, and consumers desire low-maintenance landscapes with plants suited to their environment. The Great Plains can be a challenging environment for ornamental landscape plants. Viburnum plants were potted into 2-gal (6.3 L) containers during the summer of 2012 with field trials installed Fall 2012. Field-study sites were selected to capture variability in precipitation and temperature across Kansas. Field trials in Eastern Kansas had greater survival. Shaded sites resulted in larger plants and greater survival. Plants designated for greenhouse drought and heat trials were overwintered in an unheated hoop-house the winter of 2012. Drought and heat trial cultivars were selected based on performance in field-trials as well as one Southern ecotype spp. for comparison. Drought and heat trials were conducted within a controlled greenhouse environment (Manhattan, KS) during June 2013 and April 2014, respectively. Plants acclimated in a greenhouse maintained at 25C/18C (77F/64F; day/night) for 28 days and were watered as needed until treatments were initiated. Viburnum dentatum, V. nudum, and V. tinus were exposed to both heat and drought separately. Results indicate that V. nudum responded to drought stress by reducing biomass, though photosynthetic capacity was not significantly affected. Viburnum dentatum was able to maintain similar shoot growth with moderate drought (MD) and severe drought (SD), while root growth significantly declined. Whole plant responses to increased day/night temperatures during acclimation prior to temperature curve measurements resulted in growth of all species slowing compared to control plants. All acclimated plants exhibited increased temperature optimum for Pnet with a less severe rate of increase and decline when compared to control. Viburnum dentatum and V. nudum were species which performed well in all studies and could be recommended for use in the Great Plains.
Keywords: Viburnum; Landscape; Establishment; Drought